2016
DOI: 10.15395/mkb.v48n4.915
|View full text |Cite
|
Sign up to set email alerts
|

Luaran Penutupan Duktus Arteriosus Persisten Transkateter di Rumah Sakit Dr. Hasan Sadikin Bandung

Abstract: Saat ini penutupan duktus arteriosus persisten (DAP) transkateter merupakan terapi pilihan karena memiliki efikasi yang baik, masa rawat yang singkat, risiko yang lebih rendah, dan bebas dari parut dada. Tujuan penelitian ini adalah mengevaluasi luaran jangka pendek dan menengah penutupan DAP transkateter. Penelitian merupakan laporan deskriptif analitik pasien yang menjalani penutupan DAP transkateter secara konsekutif di RS Dr. Hasan Sadikin Bandung selama periode Mei 2011 sampai dengan Juni 2014 dengan mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…9 A study in Dr. Hasan Sadikin Hospital, Bandung, West Java, Indonesia showed that transcatheter PDA closure was safe and effective in short and moderate follow up, thus it is the standard of treatment, especially in medical centers with limited ward capacity. 10 A study conducted in Ain Shams University Hospital, Egypt, showed that after PDA transcatheter closure, systolic and diastolic function were significantly decreased, but still reversible and returned to normal 1 month after closure. 11 Other studies that assessed systolic function after transcatheter closure had similar results.…”
mentioning
confidence: 99%
“…9 A study in Dr. Hasan Sadikin Hospital, Bandung, West Java, Indonesia showed that transcatheter PDA closure was safe and effective in short and moderate follow up, thus it is the standard of treatment, especially in medical centers with limited ward capacity. 10 A study conducted in Ain Shams University Hospital, Egypt, showed that after PDA transcatheter closure, systolic and diastolic function were significantly decreased, but still reversible and returned to normal 1 month after closure. 11 Other studies that assessed systolic function after transcatheter closure had similar results.…”
mentioning
confidence: 99%